BURROWING FAUNA OF BENGKALIS INTERTIDAL FLATS IMPACTED BY PEATLAND EROSION WITH PARTICULAR REFERENCE TO CRABS AND MUDSKIPPERS - Radith Mahatma; Ahmad Muhammad; Khairijon Khairijon; Sigit Sutikno; Koichi Yamamoto (JURNAL ENGGANO, 2021)
Burrowing fauna inhabiting the intertidal flats, such as certain crabs and mudskippers, are  biotic  component of intertidal ecosystem with a crucial ecological role. Their burrowing activity increases the porosity of intertidal substrates that promotes oxygenation, sediment dynamics, nutrient transport, and carbon storage. These positive contributions could however be disrupted by the degradation of their habitats as may be induced by coastal erosion. In the case of Bengkalis Island in Riau Province, Indonesia, coastal peatland erosion has generated a huge amount of peat debris that is eventually deposited on intertidal flats.  The present study has been conducted to explore burrowing crabs and mudskippers inhabiting the island’s intertidal flats most likely impacted by the deposition of peat debris. Two transect line, between the highest and the lowest tide, were made in two locations (Perepat Tunggal and Selat Baru). Observation were conducted along the transect line at interval of 5 m. Our inventory in two study locations, Perepat Tunggal and Selat Baru, has confirmed the presence of at least seven species of fiddler crabs (Austruca annulipes, Gelasimus vocans, Tubuca Bellator, T. coarctata, T. forcipata, T. paradussmieri, and T. rosea), one species of soldier crab (Dotilla myctiroides), and five species of mudskippers (Periopthalmodon schlosseri, Periophthalmus argentilineatus, P. chrysospilos, P. gracilis, P. variabilis. Our presentation shares the results in details and discusses how the disturbances induced by coastal peatland erosion might affect such fauna.Keywords: fiddler crabs, soldier crabs, mudskippers, peat debris deposition